2017
DOI: 10.1007/s13675-017-0082-6
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating balancing on social networks through the efficient solution of correlation clustering problems

Abstract: One challenge for social network researchers is to evaluate balance in a social network. The degree of balance in a social group can be used as a tool to study whether and how this group evolves to a possible balanced state. The solution of clustering problems defined on signed graphs can be used as a criterion to measure the degree of balance in social networks and this measure can be obtained with the optimal solution of the Correlation Clustering (CC) problem, as well as a variation of it, the Relaxed Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 68 publications
(122 reference statements)
0
35
0
Order By: Relevance
“…First, by applying our method more systematically to the whole EP dataset. This could cause some computational issues when solving the Correlation Clustering problem, but these could be solved by using an approximate method in lieu of Ex-CC [54]. Second, we observed that when applying k-medoids with an increasing k value, the obtained series of clusterings is almost hierarchical: it might be more appropriate to directly apply a hierarchical clustering algorithm instead.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…First, by applying our method more systematically to the whole EP dataset. This could cause some computational issues when solving the Correlation Clustering problem, but these could be solved by using an approximate method in lieu of Ex-CC [54]. Second, we observed that when applying k-medoids with an increasing k value, the obtained series of clusterings is almost hierarchical: it might be more appropriate to directly apply a hierarchical clustering algorithm instead.…”
Section: Resultsmentioning
confidence: 96%
“…there is a weighted link between each pair of nodes. Some authors prefer to extract signed vote similarity networks, which means that a weight can be positive, but also negative [4,34,54,55,58,63]. In their similarity function, they count agreement positively and disagreement negatively.…”
Section: Referencesmentioning
confidence: 99%
See 3 more Smart Citations